SHOULD BANK DIVERSIFY THEIR INCOME AND CREDIT? EVIDENCE FROM INDONESIA BANKING INDUSTRY - Fadli, Jul Aidil (KINERJA, 2019)
This study aims to examine the effect of income and credit diversification toward bank risk and performance. In this study, diversification was measured using Adjusted Herfindahl-Hirschman Index (AHHI). Bank risk is measured by the standard deviation of ROA, standard deviation of ROE, Z-Score, Nonperforming Loan and Beta. Meanwhile, bank performance is measured by Return on Assets, Return on Equity, risk adjusted ROA and risk adjusted ROE. The robustness test completes this study by dividing the sample into low and high diversified bank. By using panel data of 53 listed and non listed Indonesian banks from 2011 to 2015, the results show that banks get benefit through the implementation of income diversification. Conversely, banks are badly affected through the implementation of loan diversification as it can increase risk and decrease bank performance. The results suggest bank to maximize income diversification by increasing the proportion of non-interest income in the income structure. Furthermore, banks should focus credit distribution that best suits their capabilities.Keywords: bank, credit, diversify, interest income